Multi Hazard Analysis of Ponorogo Regency Disaster Based on Geographic Information System - Bayu Fikri Hanafi; Kuswaji Dwi Priyono (International Journal for Disaster and Development Interface, 2023)
Ponorogo regency has dangers to several types of disasters such as floods, landslides, tornadoes, land fires, and droughts. Based on data from BNPD from the period 2000 - 2020, Ponorogo Regency has experienced 123 landslides, and 39 flood disasters. The approach used in this study is multi-hazard disaster. The purpose of the study is 1.) Analyze the spread of flood hazard levels in Ponorogo Regency. 2.) Analyze the spread of the danger level of landslide disasters in Ponorogo Regency.3.) Analyze the distribution of disaster hazard levels in Ponorogo Regency using a multi hazard index. The research methods conducted in this study are stacking and improvement, while for multi-hazard modeling of disasters using VCA tables. Data processing in this study is divided into 3 stages, namely parameter data processing, disaster hazard data modeling, and multi-hazard disaster modeling. The accuracy test is conducted on the usage data, and the sampling method is a random sampling method. Validation tests were conducted on data from modeling the hazards of floods and landslides. The results of this study are a disaster parameter data map, a flood hazard map, a landslide hazard map, and a multi-hazard disaster map. Based on the results of modeling, multi-hazard disaster has an area that is low hazard class has the widest area of 90,773.55 Ha (65%), The moderate hazard class has an area of 45,438.55 Ha (33%). The high hazard class has an area of 2,957.56 Ha (12%). The multi-hazard class is determined by the result of a combination of landslide and flood hazard classes, for example the combination of low and high hazard classes will produce a moderate hazard class. Therefore, the distribution of areas from the multi-hazard class of disasters is greatly influenced by the distribution of areas of both types of disasters.